OC-017 International Multicentre Study Assessing the Effects of Anti-Thrombotic Use in Patients with Upper GI Bleeding. (17th August 2016) - Dunne, P; Laursen, SB; Laine, L; Dalton, H; Ngu, JH; Schultz, M; Murray, I; Rahman, A; Anderloni, A; Stanley, A
Abstract : Introduction: Anti-thrombotics (antiplatelets and anticoagulants; ATs) have been identified as risk factors for upper gastrointestinal bleeding (UGIB). However few international studies have evaluated their effect on patient outcome. We aimed to assess the effects of AT use on outcome in patients with high-risk UGIB requiring endoscopic therapy. Methods: Patients presenting with UGIB who required endoscopic therapy at eight centres (Scotland, England, USA, Canada, Denmark, Italy, Singapore & New Zealand) were prospectively included over 12 months. Data recorded included the full Rockall score (FRS); AT use (Aspirin, Adenosine Diphosphate Receptor Inhibitors (ADP-RI), Vitamin-K Antagonists (VKA), Low Molecular Weight Heparin (LMWH), Thrombin inhibitors and Factor Xa inhibitors); endoscopic findings; blood transfusion; interventional radiology; surgery; rebleeding; 30 day mortality and length of hospital stay. Results: Out of 3154 patients, 619 required endotherapy (44% for ulcer bleeding and 21% for varices). 187 (30%) patients were on aspirin, 61 (11%) ADP-RI, 57 (9%) VKA, 8 (1%) LMWH, 7 (1%) factor Xa-inhibitor and 1 patient a thrombin-inhibitor. 63 (11%) patients were treated with >1 type of AT. Patients treated with ATs were older (p < 0.0001), had higher ASA-score (p = 0.001), lower haemoglobin (P = 0.04), higher FRS (p < 0.0001), more frequently had ischaemic heart disease (IHD; p < 0.001), less frequently had cirrhosis (P < 0.001), more frequently bled from ulcers (p < 0.001) but less frequently from varices (p < 0.001) compared with those not taking ATs. There were no differences in sex, systolic blood pressure, frequency of malignancies, need for surgery/embolisation or rebleeding rate. Patients taking ATs had lower mortality than those not taking these drugs: all cause (11/253 [4%] vs 37/315 [12%]; p = 0.006) and bleeding-related (3/253 [1%] vs 19/315 [6%]; p = 0.01). However, when excluding patients with liver cirrhosis (n = 151) there were no differences in mortality between groups. Conclusion: Patients with UGIB who require endoscopic therapy whilst on ATs do not experience a higher rate of rebleeding or mortality compared with UGIB patients who do not use ATs. We observed excess mortality in patients not taking ATs, which is likely due to the high rates of cirrhosis (40%) and variceal bleeding (33%) in these patients. Further studies are needed to clarify the risk of adverse outcome following UGIB in patients taking novel ATs. Disclosure of Interest: None Declared